Temporal trends and spatial heterogeneity of sanitation facilities in Ethiopia: evidence from the 2005–2019 Demographic and Health Surveys - Jember Azanaw; Mesenbet Tsegaye; Wodage Mesele (BMJ Open)
Background The main aim of sanitation is to prevent human contact with faecal pathogens to decrease occurrences of diseases. However, no region in the world is on the right track to accomplish Sustainable Development Goal (SDG) 6.2 for universal access to sanitation. Sub-Saharan Africa, including Ethiopia, is significantly behind in meeting the 2030 SDG 6.2 targets. Hence, this study focused on the spatial and temporal analysis of sanitation in Ethiopia based on four demographic health surveys.Design This research was undertaken among households in Ethiopia based on a weighted sample size. Variables with a p<0.2 in bivariable analysis were incorporated into the multivariable analysis. Subsequently, a 95% CI and a p<0.05 were used to assess the statistical significance of the final model. Global and local indicators of spatial correlation were done. Statistical analyses were performed by using STATA V.17 and ArcGIS V.10.7 software.Results This study includes data from 13 721 households in the 2005 Ethiopian Demographic and Health Survey (EDHS), 16 702 households in the 2011 EDHS, 16 650 households in the 2016 EDHS and 8663 households in the 2019 EDHS. The prevalence of improved sanitation facilities in Ethiopia was 20.46%, 25.61%, 25.86% and 27.45% based on EDHS 2005, 2011, 2016 and 2019, respectively. Global Moran’s I spatial autocorrelations, hotspots and spatial interpolation analysis indicated the inequality of improved sanitation facilities. Educational status of primary (adjusted OR, AOR 2.43, 95% CI 2.00, 2.95), secondary (AOR 2.02, 95% CI 1.61, 2.54) and higher (AOR 4.12, 95% CI 3.35, 7.54), watching television (AOR 5.49, 95% CI 4.37, 6.89), urban areas (AOR 9.08, 95% CI 6.69, 12.33) and region were factors statistically associated with sanitation facilities.Conclusion The overall finding of this study concludes a very slow increment in sanitation facilities over time and the presence of geographical heterogeneity in Ethiopia. Educational status, watching television, wealth index, community-level education, type of residence and region were factors statistically associated with sanitation facilities.